THE PROBLEMS IN TEACHING LANGUAGE - Jumaniyazova Nargiza Abdugofurovna; Mavlonova Shahzoda Turgunovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article, we will talk about the methodology of teaching a foreign language, modern types of techniques used in the methodology of teaching a foreign language, and their use.